2016
DOI: 10.1039/c6ce00013d
|View full text |Cite
|
Sign up to set email alerts
|

Ambient controlled synthesis of advanced core–shell plasmonic Ag@ZnO photocatalysts

Abstract: Plasmonic Ag@ZnO core-shell hybrids, including hetero-nanowires and hetero-nanoparticles, have been synthesized at room temperature for application in photocatalysis. The morphology, size, crystal structure, and composition of the products were investigated by X-ray diffraction, scanning and transmission electron microscopy, X-ray photoelectron spectroscopy, and ultraviolet-visible spectroscopy. It was found the concentration of Zn(NO3)2·6H2O and the amount of water play crucial roles in the formation of Ag@Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…On the other hand, for pure ZnO, rapid recombination of photoexcited electrons and holes weakens its photocatalytic efficiency. To solve this problem, one of the most efficient ways is to modify ZnO using noble metals such as Pt, Pd, Au,, and Ag to form metal/ZnO heterostructures. When metal and semiconductor materials are combined with each other, a Schottky barrier will be formed between metal and semiconductor, which can improve charge separation and thus enhance the efficiency of the degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for pure ZnO, rapid recombination of photoexcited electrons and holes weakens its photocatalytic efficiency. To solve this problem, one of the most efficient ways is to modify ZnO using noble metals such as Pt, Pd, Au,, and Ag to form metal/ZnO heterostructures. When metal and semiconductor materials are combined with each other, a Schottky barrier will be formed between metal and semiconductor, which can improve charge separation and thus enhance the efficiency of the degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…41 In a typical synthesis, 10 mL of 1,2-propanediol containing PVP40 was loaded into a 25 mL vial and heated with magnetic stirring in an oil bath at 135°C for 1 h. NaCl was then quickly added, and the stirring was continued for another 5 min, followed by the addition of AgNO 3 solution. The mixed solution was then heated at 135°C with magnetic stirring for 1 h, yielding the grey Ag NWs.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Ag nanostructures exhibit a wealth of optical and photoelectrochemical properties directly related to their geometry- 36 and Ag-ZnO. 41 Although there are a few reports on the degradation of organic pollutants by Ag-CdS hybrids, 25,26 there is still no report on highly efficient heterostructured photocatalysts based on a 1D Ag@CdS coreshell hierarchical architecture, which might be able to fully take advantage of the 1D hierarchical nanostructure. Inspired by the hierarchical structure of the natural photosynthetic system, 1D Ag@CdS core-shell photocatalysts with hierarchical nanostructures were prepared by a simple wet chemistry approach in this work.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the surface plasma resonance absorption of the Ag@ZnO nanostructures can be tuned with different sizes and morphologies of ZnO shells coating the Ag cores, and their photo-luminescent phenomenon is studied in detail; 20 Jin Yan Xiong et al have adopted a convenient chemical route to prepare stable and highly efficient solar light driven core-shell Ag@ZnO nanoparticle, which shows higher photo-catalytic activity than pure ZnO nano-crystal under solar light irradiation. 16 Yi Mai Liang and their coworkers use a facile two-step method to prepare the three-dimensional flower-like Ag/ZnO heterostructure with different Ag content. The results demonstrate that Ag/ZnO heterostructure not only improve photocatalytic activity, and exhibit good recycling stabilities over several separation cycles photodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Among all kinds of noble metals, Ag is particularly suitable for construction of novel noble metal/semiconductor hetero-nanostructure, owing to the low cost and a wealth of optical and photoelectron chemical properties of Ag relate to other noble metals. [14][15][16] Until now, lots of research work has been performed to design and construct different Ag-core/ZnO-shell configurations, and those of the physic chemistry properties are explored. For instance, Sourav Das and their coworkers have synthesized Ag@ZnO core-shell nanostructure for the solar photo-catalytic disinfection of water borne pathogens, these structures have shown superior photo-catalytic ability for oxidation of volatile organic compounds; 17 Matías E. Aguirre et al have well-defined Ag@ZnO core-shell architectures, confirm that the presence of Ag nanoparticles in the core-shell nanostructures conduces to slow down charge recombination both under UV and visible light excitation; 18 Manuel Macias-Montero et al present a new type of nanostructures consisting of supported hollow ZnO a These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%